ANALISIS PERMENDIKNAS NOMOR 16 TAHUN 2007 DALAM RANGKA MENJAMIN STANDARISASI KUALIFIKASI AKADEMIK DAN KOMPETENSI GURU DI KABUPATEN KEPULAUAN SULA - Mohbir Umasugi; Mardiyono .; Sarwono . (REFORMASI, 2014)
Education is basic requirement for nation in an effort to improve the quality of human resources. Goverment efforts in improving the quality of education for Indoneisa is the issuance of law number 20/2003 as a refinement of the law number 20/1989 on the national education system, to achive national education goals, the goverment set national standards set out in the education regulation number 19/2005 about nasional education standards. So as to improve the quality of teachers born regulation of the Minister of National Education Number 16/2007 about the academic qualification standards and competence requaired for continuing education bachelor. The research is a study on policy implementation standards and competencies of academic qualifications teacher in accordance with the regulation of education minister number 16/2007 about academic qualification standards and competencies of theachers and supported by the Sula Island City regulation number 9/2008 concerning the duties and functions of the department of education.